Filling Ability of Various Root Canal Sealers into Simulated Lateral Canals: An In Vitro Study - Nur Ayad Alalaf; Emad Farhan Alkhalidi (Wolters Kluwer Medknow Publications, 2022)
Background: This study aimed to assess and compare the depth of penetration of TotalFill BC, AH Plus Jet, and GuttaFlow Bioseal sealers into simulated lateral canals. Materials and Methods: A total of 30 extracted mandibular premolars were selected. Simulated lateral canals were made. The specimens were randomized into three experimental groups of 10 each. The specimens were cleared for visualization under a stereomicroscope at 10× magnification. The depth of penetration was assessed by a four-grade scoring system. Data were submitted to Fisher exact test at 5% significance. Results: There was statistically no significant difference among the experimental groups regarding the depth of penetration (P > .05). Conclusion: All root canal sealers experimented with herein showed a comparable depth of penetration in the simulated lateral canals regarding their filling ability.